Review on Soft Computing in Data Analysis - Joseph, S. Iwin Thanakumar (Journal of Ubiquitous Computing and Communication Technologies, 2022)
The ability to access, store, and process enormous volumes of data has significantly expanded due to technological advancements in computation, data storage, networks, and sensors. Large-scale data processing is becoming an increasingly important thing for both research and business. Clients, who are typically domain experts, face an enormous challenge and require assistance in handling huge amount of data’s. Soft computing can indeed be characterised as a science of thought and logic that aids in navigating complex systems. This article is about the use of soft computing techniques to support data analysis in an intelligent manner.